Long division - McElroy, Gil (Brave & brilliant series, 2020)
"Long Division is a book of poetic commentary that plots a steady course of disillusion. Working in explicit dialogue with Dada, the surrealist poets, spiritual writing, and drawing on midrash as a wellspring, Gil McElroy captures in poetry the process of a mind in thought. Written in asides and afterwords, comments and commentaries, and interruptions and insertions, these poems challenge and disrupt meaning and intention. Carefully planned and written with an easy confidence, these poems ruminate on time and chance, astronomy and biology, intertextuality and the interplay of the author's and reader's voice. They interrogate and are, themselves, an internal interrogation through which division wends, splitting words into new units of meaning or reassembling them into new shapes unencumbered by the halos of meaning, reference, and allusion they have accrued. This is contemporary experimental poetry at its finest, at once abstract and distinct, celestial and personal, a drama of the mind as it engages with and responds to the world and time. Long Division takes what is complex and explores its simplicity before taking what is expected to be simple and showing it instead to be musical and strange."--